Enteropathic Arthritis Accompanied by Tuberculous Colitis: A Case Report - Agung Sandi Ramadan; Cahyo Wibisono Nugroho (Gastro Hep Advances)
Enteropathic arthritis (EnA) is a type of spondyloarthritis with inflammatory bowel disease, such as ulcerative colitis and Crohn’s disease, which is challenging to differentiate from tuberculous colitis. Patients with EnA living in endemic tuberculosis have a high risk of tuberculosis infection (tuberculous colitis), which triggers a recurrent increase in disease activity. Discontinuation of corticosteroid therapy in EnA and early start to antituberculosis drugs are recommended in the patients. Complete treatment of tuberculosis helps improve the prognosis of tuberculous colitis. Patient compliance in treatment plays a crucial role in managing tuberculous colitis exacerbated by EnA in endemic areas.